2023
DOI: 10.3389/fendo.2023.1202917
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of high-dose intramuscular vitamin D2 injection in type 2 diabetes mellitus with distal symmetric polyneuropathy combined with vitamin D insufficiency: study protocol for a multicenter, randomized, double-blinded, and placebo-controlled trial

Abstract: BackgroundDistal symmetric polyneuropathy (DSPN) is the most common chronic complication of type 2 diabetes mellitus (T2DM). DSPN may lead to more serious complications, such as diabetic foot ulcer, amputation, and reduced life expectancy. Observational studies have suggested that vitamin D deficiency may be associated with the development of DSPN in T2DM. However, interventional studies have found that low-dose vitamin D supplementation does not significantly improve neuropathy in DSPN. This study aims to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Controlling blood glucose alone cannot prevent the progression of peripheral neuropathy in T2DM. Chen T ( 37 ) found that monthly intramuscular injections of high-dose vitamin D improved peripheral neuropathy. This may provide new ideas for treating diabetic peripheral nerves.…”
Section: Relationship Between Vitamin D Levels and Diabetesmentioning
confidence: 99%
“…Controlling blood glucose alone cannot prevent the progression of peripheral neuropathy in T2DM. Chen T ( 37 ) found that monthly intramuscular injections of high-dose vitamin D improved peripheral neuropathy. This may provide new ideas for treating diabetic peripheral nerves.…”
Section: Relationship Between Vitamin D Levels and Diabetesmentioning
confidence: 99%